2017
DOI: 10.1016/j.eats.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Patellar Tendon Repair: Internal Brace Technique With Unicortical Buttons and Suture Tape

Abstract: Patellar tendon ruptures may be considerably limiting, especially in younger and highly active patients. These injuries ultimately result in a complete inability to maintain extension of the knee, thereby placing strict impediment on physical activity. As a result, a durable repair construct via surgery is necessary to allow patients to return to their preinjury activity level. Because of the inherent difficulty in maintaining patellar tendon position after repair, and to avoid failure of the tendon healing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Our observation has been confirmed by earlier experimental measurements on wounded ligaments, and threose treated cartilage, in which a clear positive correlation between crosslink density and tissue strength has been well documented 56,57 . Our predicted patterns of micro damage (plastic change) are in line with the previously reported ligament failure patterns 58‐64 . The patellar tendon was the only structure characterized by connective tissue–bone boundary failure, in which the fibers fail at the tendon‐bone junction without fracture of the underlying bone.…”
Section: Discussionsupporting
confidence: 90%
“…Our observation has been confirmed by earlier experimental measurements on wounded ligaments, and threose treated cartilage, in which a clear positive correlation between crosslink density and tissue strength has been well documented 56,57 . Our predicted patterns of micro damage (plastic change) are in line with the previously reported ligament failure patterns 58‐64 . The patellar tendon was the only structure characterized by connective tissue–bone boundary failure, in which the fibers fail at the tendon‐bone junction without fracture of the underlying bone.…”
Section: Discussionsupporting
confidence: 90%
“… 12 , 13 , 14 , 15 Suture augmentation repair has also been described with the standard Krackow transosseous technique for patellar tendon repair. 16 One biomechanical study found that the Krackow technique with high-strength suture tape augmentation was stronger than cerclage wire augmentation or the Krackow technique alone in repair of midsubstance patellar tendon rupture. 17 A separate technique article described a patellar tendon repair method using a high-strength suture tape construct with unicortical buttons for fixation.…”
Section: Introductionmentioning
confidence: 99%
“… 17 A separate technique article described a patellar tendon repair method using a high-strength suture tape construct with unicortical buttons for fixation. 16 However, the role of high-strength suture tape augmentation of the Krackow technique in the setting of inferior pole avulsion remains unclear. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Another group of knee surgeons published a surgical technique also advocating the use of suture tape as reinforcement in the reconstruction of the patellar tendon, suggesting better results with the tape. 27 Reconstruction of the patellar tendon using adjustable suspensory fixation has been reported for the treatment of chronic lesions. 28 The authors of this technique advocated the use of autologous semitendinosus and gracilis grafts.…”
Section: Discussionmentioning
confidence: 99%